Metode Agile Dalam Perancangan Sistem Informasi Reservasi Fasilitas Universitas Advent Indonesia - Kevin Oloan Simatupang; Andrew Fernando Pakpahan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The Indonesian Adventist University Facility Reservation Information System is designed and designed to provide services and convenience in terms of managing and managing the facilities available at the Indonesian Adventist University and reducing data collection that is still done manually in order to improve performance efficiency and online adjustments. WhatsApp is a social media platform that most people are interested in because it is easy to access and looks friendly to visitors. This information system is designed using the Agile method and notifications will be sent via WhatsApp with details regarding the results of the facilities ordered. The results of the study are that organizational management can order facilities and notifications will automatically be sent to WhatsApp for those who order and do not need to spend paper to print licensing letters and time to go to various superior rooms to ask for approval.